IMPROVEMENT INTEGRATED PROGRAM (PIM) IN CONSTRUCTION COMPANIES - Sarmiento, Alfredo (Revista Ingeniería de Construcción, 2001)
This paper discusses a model called Improvement Integrated Program (PIM) which has been designed in order to introduce improvement processes based on an integrated approach in both companies and their projects. This Program establishes and structures different stages, involving basic activities and tools aimed at attaining a company’s goals and targets. As such, this model has developed from recent consulting assignments in Chilean construction companies and, hence, it is adapted to industry-specific cultural and technological issues. The main stages, which act in an articulated and complementary manner are: a) Strategic Planning. b) Re Design and Up Grade of Practices and Processes (Business Process Reengineering) c) Improvement Program in the Company, compounded by: Quality Improvement Program, Productivity Improvement Program, Operational Planning Improvement Program. d) Control and Evaluation of Countermeasures. These pilot experiences have shown that this integrated approach has not only made it easier to implement the different stages, but also increased personnel’s commitment on account of their involvement in defining programs, thus leading to better and more efficient results than those arrived at with isolated programs, Also, it is worth mentioning that PIM makes it possible to include and integrate other current and related areas, such as Environmental, Safety and Health Programs, among others so as to offset the impact of change within the company.